Pengasuhan orang tua anak usia dini di era disrupsi - Mustakim Mustakim; Hamim Farhan; Agustien Lilawati; Ode Mohamad Man Arfa Ladamay; Musayyachah Musayyachah; Rina Sekar Pratiwi (University of Islam Malang, 2021)
Advances in technology and the times are increasingly global, require parents to adapt quickly to the changing times. The childcare has traditionally had started at the left along with the era of increasingly apparent disruption in sight. Parenting training objectives early childhood in an era of disruption is a response from the busyness of parents in making a living, rapid advances in technology, the rise of gadgets, social media, youtube, online games, and negative news. Training delivery methods using lectures, discussions and brainstorming group. Training processes with the assessment phase, the implementation phase, and the phase of assessment and evaluation phase. Training results illustrate that parents have started to realize the education of children in the age of disruption, the use of technology-based smart parenting, immune selfer, character education and religious values in accordance with the teachings of the Prophet. Parents educate children to have manners, polite, obedient worship, and establish good relationships with others, as well as parents provide love, security, smart in dealing with the times.